An energy-optimal solution for transportation control of cranes with double pendulum dynamics: Design and experiments. (1st March 2018) - Sun, Ning; Wu, Yiming; Chen, He; Fang, Yongchun
Highlights: The paper firstly achieves energy-optimal control for double pendulum cranes. The system state constraints are taken into consideration. Hardware experiments verify the effectiveness of the proposed method. Abstract: Underactuated cranes play an important role in modern industry. Specifically, in most situations of practical applications, crane systems exhibit significant double pendulum characteristics, which makes the control problem quite challenging. Moreover, most existing planners/controllers obtained with standard methods/techniques for double pendulum cranes cannot minimize the energy consumption when fulfilling the transportation tasks. Therefore, from a practical perspective, this paper proposes an energy-optimal solution for transportation control of double pendulum cranes. By applying the presented approach, the transportation objective, including fast trolley positioning and swing elimination, is achieved with minimized energy consumption, and the residual oscillations are suppressed effectively with all the state constrains being satisfied during the entire transportation process. As far as we know, this is the first energy-optimal solution for transportation control of underactuated double pendulum cranes with various state and control constraints. Hardware experimental results are included to verify the effectiveness of the proposed approach, whose superior performance is reflected by being experimentally compared with some comparative controllers.